Corporate Governance Issues: Disclosure and Transparency. An Interdisciplinary Approach (European Journal of Marketing and Economics, 2020)
Two of the pillars of contemporary corporate governance are examined in this article – disclosure and transparency. Though an interdisciplinary approach, knowledge from different fields of the economic science are brought together in order better clarify the interdependence and the level of interaction between these. Knowledge traditionally considered to be part of the Corporate Governance (disclosure and transparency and what is most modern nowadays - ESG) is examined form the perspective of the governance bodies and other stakeholders, taking into account tools from the fields of sustainable development, project management and marketing. The processes of digitalization also find their reflection in the current article. The case study approach is used to illustrate the interdisciplinary interaction.
Keywords: Corporate Governance, Disclosure, Transparency, ECG